1996
DOI: 10.1083/jcb.134.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Biology of chemokine and classical chemoattractant receptors: differential requirements for adhesion-triggering versus chemotactic responses in lymphoid cells.

Abstract: Abstract. Several chemoattractant receptors can support agonist-induced, integrin-dependent arrest of rolling neutrophils in inflamed venules in vivo, as well as subsequent crawling into tissues. It has been hypothesized that receptors of the Goq-linked chemoattractant subfamilies, especially receptors for chemokines, may mediate parallel activation-dependent arrest of homing lymphocyte subsets. However, although several chemokines can attract subsets of B or T cells, robust chemoattractant triggering of resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(178 citation statements)
references
References 49 publications
10
166
0
2
Order By: Relevance
“…It has been shown that the stimulation of IL-8 receptor transfectants by IL-8 causes transient integrin activation (24). It was found that 5A12, 7D9, and 6C6 were able to inhibit IL-8-induced VCAM-1 binding of the CXCR1 or CXCR2 transfectants by 35-50% (data not shown).…”
Section: Generation Of Anti-cxcr1 and -Cxcr2 Mabs That Can Block The mentioning
confidence: 89%
See 2 more Smart Citations
“…It has been shown that the stimulation of IL-8 receptor transfectants by IL-8 causes transient integrin activation (24). It was found that 5A12, 7D9, and 6C6 were able to inhibit IL-8-induced VCAM-1 binding of the CXCR1 or CXCR2 transfectants by 35-50% (data not shown).…”
Section: Generation Of Anti-cxcr1 and -Cxcr2 Mabs That Can Block The mentioning
confidence: 89%
“…Chimeric CXCR1/2-For stable transfectants, the murine pre-B lymphoma cell line (L1-2) was used and transfected as described (24,25 Antibodies and Flow Cytometry, Isolation of Neutrophils-Anti-CXCR1 and -CXCR2 antibodies were generated as described (23). In addition, two previously reported (21) anti-CXCR2 mAbs, 10H2.12.1 (ATCC HB-11494) and 4D1.5.7 (ATCC HB-11495) were used for the purpose of comparison.…”
Section: Creation Of Cell Lines Stably or Transiently Expressing Wt Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration Assay-Migration of BaF3 cells was assessed using the Transwell assay system as described previously (5,22). Briefly, cells were washed and resuspended in RPMI 1640 containing 0.2% bovine serum albumin and 10 mM HEPES buffer at a density of 5 ϫ 10 6 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, microarray results showed that IL-10 increased mRNA levels of adhesion/migration-related genes such as L-selectin, VEGF receptor-1, t-PA, HM74, formyl peptide receptor-1 and lipoxin A4 receptor (Figure 3). The last three genes are involved in the synthesis of peptide receptors [38][39][40] that mediates leukocyte chemotaxis by binding peptides derived from protein degrada- tion occurring in damaged/diseased areas. 41 The overexpression of these receptors might play an important role in NK cell migration in response to the liberation of danger signals (eg peptides) freed in the tumor microenvironment.…”
Section: Genementioning
confidence: 99%